Pembuatan Media Pembelajaran CD Interaktif Dalam Bentuk Game Pada Sub Pokok Bahasan Reaksi â reaksi Hidrokarbon Di Kelas X SMA - Yuhelman, Nofri; Bakar, Usman; Oktavia, Budhi (Jurnal Zarah, 2015)
This research aims to produce a medium of learning in the form of game CD Interactive discussion on part of the subject hydrocarbon reactions to senior high schools that can be used as a medium of learning and to find out its feasibility. Interactive CD media in the form of the game was created using Macromedia Flash 8 program. This type of research is done is research Research and Development (R&D), the research methods used to produce a particular product, and test the effectiveness of the product. Interactive CD in a game that made ââ30 people tested for class XI science students SMA Negeri 1Batang Ana it he terms of form, motivation, and practicality. Terms of the content by theUNP chemistry lecturer, chemistry teachers SMA Negeri 1Batang Anai, chemistry teachers from other schools that are all a total of 11students majoring in chemistry and a total of 30 people. The instrument used was questionnaire in the form of Likert scale. Feasibility of the media are made of the analytical results obtained by questionnaire lecturer and teacher at 3.45, from 3.46 for the student questionnaires, and questionnaires from students majoring in chemistry at 3.40. The results showed that the Interactive CD media in the form of this game is worthy of discussion part of the subject used in hydrocarbon reactions both in terms of shape/appearance, content, motivation and practicality.